Kaupunkinimistön tutkimuksen perusteet - Ainiala, Terhi (Virittäjä, 2003)
The study of urban names (englanti) 2/2003 (107) The study of urban names The article examines the fundamental nature of urban names and proposes a set of goals, methods and research questions for the study of urban names in Finland. Urban names constitute a new research field in Finnish onomastics, which has hitherto focused mainly on rural names. The study of urban names is concerned with both the official and the unofficial nomenclature. Unofficial names are those names in the urban environment that have no official status but are used by the inhabitants in their everyday speech. The study of urban names deals above all with socio-onomastic aspects: the use of names, knowledge of names and variation in names. The writer examines the formation of names in the unofficial nomenclature. Unofficial names are secondary names if they are devised on the basis of an official name (e.g. Lnnrotinkatu > Lnkka); other unofficial names are primary names describing particular places. Some names will include both primary and secondary features. Unofficial urban names have many of the same features as slang. They may play with language, contain humour or irony, or be used to express different attitudes (e.g. the restaurant name Humppahelvetti; humppa name of a Finnish dance + helvetti hell). The function of an unofficial name is not, of course, solely to identify a place. Often they may be affectionate names or indicators of group identity. The article also presents a number of possible research questions for this field of study. These include investigation of the extent and status of unofficial names in comparison with the official nomenclature, and there are also important questions regarding the giving and use of names. Who labels places with particular names and who uses the names? Are there differences in name usage from one group of people to another? What kind of attitudes and values are revealed in the unofficial urban nomenclature? The writer notes that although the strongest research connection in the study of urban names is with the study of rural names, the field will nevertheless have to adopt research methods that differ to an extent, because of the particular characteristics and differences involved when dealing with urban names. Research on urban names can also be seen as part of the urban studies field. Terhi Ainiala Kielenainekset -(k)kA (kieli: suomi, sivulla: 211) -Ari (kieli: suomi, sivulla: 211) -is (kieli: suomi, sivulla: 211) -tsi (kieli: suomi, sivulla: 211) -tsu (kieli: suomi, sivulla: 211) Aakoo (kieli: suomi, sivulla: 212) Ala-Leikkis (kieli: suomi, sivulla: 213) amis (ki